MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS MAHASISWA PTIK MELALUI PEMBELAJARAN BERBASIS MASALAH - Evan Farhan Wahyu Puadi (Program Studi Pendidikan Matematika STKIP Muhammadiyah Kuningan, 2016)
Discrete mathematics is one of the basic theories that supports computer science. Meanwhile, students of the Faculty of Computer Science generally still think that discrete mathematics is a parallelized subject of computer science, so that the majority of students' mathematical problem solving abilities have not optimal. To change this reality, we need an innovation in lectures, one of which is to apply problem-based learning. This study aims to find out whether the increase in mathematical problem solving abilities of students who get based learning different problems with students who get conventional learning. The population in this study were students of the Information Systems study program at Indonesia, which is of the same level as the Faculty Information System study program University of Subang Computer Science when viewed from the value of BAN-PT accreditation, and The sample in this study were students of the Information Systems study program The Faculty of Computer Science, University of Subang, which took the Mathematics course Discrete (compulsory courses given in semester II). This research was conducted of two groups, namely the experimental group and the control group. Group the experiment is a group of students who get based learning problem while the control group is a group of students who are taught with conventional learning. The research design is in the form of a Pre-test Post-test Control Group Design. Research data was collected through tests. Results this research is (1) improvement of mathematical problem solving abilities students who get lectures with problem-based learning approaches are different from mathematical problem solving abilities of students who get conventional learning